3D printing of stretchable, ionic conductive, adhesive hydrogel with enhanced water retention for motion detection. (2022) - Lin, Congjian; Yang, Hui Ying
Abstract: Stretchable ionic conductors, including ionic conductive hydrogels, are ideal for flexible electronics. However, due to poor adhesion to human skin and quick drying in ambient conditions, the development of hydrogel-based electronics is currently constrained. This research used a digital light processing (DLP) technique to make a 3D printed ionic conductive hydrogel. The novel hydrogel's high ZnSO4 salt content improves interfacial adhesion and water retention. A sandwiched hydrogel-elastomer capacitive sensor was created to show its ability to collect body signals, which opens a new route in flexible sensors.